A new species of Escobedia (Orobanchaceae) from the state of Michoacan, Mexico - Carranza González, Eleazar; Medina García, Consuelo (Instituto de Ecología, A.C., 2008)
Escobedia michoacana (Orobanchaceae) is described as a new species from the state of Michoacán, Mexico. An illustration is also presented, together with a discussion of its affinities to other species and a key to distinguish the Mexican members of the genus. It is a rare taxon restricted to the northwestern part of the state, although it possibly occurs in adjacent Jalisco. It differs from the other Mexican species of the genus by possessing 5 (vs. 10) rib-like veins extending the length of the calyx.